Characteristics of nucleotide sequence of cystatin gene of some peanut lines derived from irradiated and dehydrated - Thu Thuy, Vu Thi; Tam, Nguyen Thi; Mau, Chu Hoang; Thanh Thanh, Nguyen Vu (Academia Journal of Biology, 2012)
Cystatin are super family of cystein protease inhibitor protein which is found in plants, animals and micro-organism. They are divided into three inhibitory families based on the difference of amino acid sequence, disunity bond and molecular weight including: the first is stefines, the second is cystatins and the third is kininogens. In plant cystatin is name phytocystatin (physic), it is also an independent brand of cystatin families on phylogenetic. Physic has very importance physiological functions such as regulation of activity of endogenous cystein protease during seed development, germination and programmed cell death. Recently, there are many researches on relationship between cystatin and resistance in plant (drought tolerance, cold tolerance, salt tolerance and ability of against pathogenic microorganisms). Analyzing and comparing cytatin gene sequences not only can provide valuable knowledge for the conservation and evaluation of the evolution of cytatin genes, but also shed light on issues related to function of cytatin protein. Isolation and sequencing cystatin gene of the L23 peanut cultivar and two lines: R4.6, M4.8 derived from callus treated with irradiation and dehydration of L18 peanut cultivar. The results showed that cystatin genes had 461 nucleotides and contained one intron between two conservative regions L22A23R24F25A26V27 and Q49V50V51A52G53. There are 28 different nucleotide positions on cystatin genes and seven amino acids on protein molecules of L23 peanut varieties and the M4.8, R4.6 lines in comparison with published sequences of peanut cystatin gene. The gene sequence encoded protein of peanut lines in this research have different levels from 2.1% to 5.2% and could be used for further research on the relationship between cystatin gene structure related to drought tolerance of peanut.